Digital Citizenship and Moral Development: Integrating Technology into Family-Based Character Education - Musyarrafah Sulaiman Kurdi (International Forum of Researchers and Lecturers, 2023)
This research explores the intricate relationship between digital citizenship, moral development, and family-based character education, focusing on integrating technology. Employing a library research approach and descriptive analysis method, the study delves into existing literature to investigate the impact of technology-based interventions on parental influences in shaping children's ethical decision-making in the digital age. The research addresses three primary questions: (1) How does incorporating technology in family-oriented character education programs impact children's formation and reinforcement of moral values and digital citizenship skills compared to traditional methods? (2) What are the key challenges and opportunities families face when leveraging technology for character education, and how do these factors influence the effectiveness of moral development within the familial environment? (3) In what ways do parental involvement and modelling of digital behaviours shape children's ethical decision-making and online conduct, and how can technology-based interventions enhance or alter these parental influences on their children's moral development and digital citizenship? Through a comprehensive review of theoretical frameworks, empirical studies, and technology integration models, this research aims to provide valuable insights into the evolving dynamics of character education within the digital landscape.